Assessing flow benefits of protected areas of central India: a case study from Maharashtra state of India. (28th August 2019) - Roy, Adrija; Yadav, Vicky; Chaudhry, Pradeep
It is a common realisation that protected areas (PAs) are playing a valuable role in maintaining biological diversity as well as providing immense economic benefits arising out of tourism and other direct uses. They are the cornerstone of most conservation strategies. They protect biodiversity, safe-guard ecosystem health, and provide an array of ecosystem services, such as fresh drinking water, places for recreation and relaxation, storehouses of genetic material, pollination, gas regulation, biological control and providing habitat and refugia for wildlife. In the present article, we have given an account of flow benefits, including employment opportunities to locals and other intangible or non-market benefits, emanating from five protected areas (national parks/tiger reserves and a sanctuary) of Maharashtra state from central India. These benefits have been analysed with the help of collected primary data and available secondary information. We understand that improved governance and appropriate investment in these areas would ultimately lead to maintaining ecological security, food security and finally sustainable development of society in long term basis.